In a HP. if the pth term is qr and qth term is pr.Prove that the rth term is pq?

Asked by  | 6th Jul, 2008, 11:11: PM

Expert Answer:

let H.P. be 1/a , 1/(a+d) , 1/(a+2d),....

then given a+(p-1)d = 1/qr

and a+(q-1)d = 1/pr

solving for a and d we get a = -1/pqr  and d = 1/pqr

then a+(r-1)d= -1/pqr + (r-1)(-1/pqr) = 1/pq

so pth term of H.P. will be 1/(a+(r-1)d) = pq

Answered by  | 12th Sep, 2008, 12:26: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.